Genetic spectrum of Saudi Arabian patients with antenatal cystic kidney disease and ciliopathy phenotypes using a targeted renal gene panel. Issue 5 (9th February 2016) - Al-Hamed, Mohamed H; Kurdi, Wesam; Alsahan, Nada; Alabdullah, Zainab; Abudraz, Rania; Tulbah, Maha; Alnemer, Maha; Khan, Rubina; Al-Jurayb, Haya; Alahmed, Ahmed; Tahir, Asma I; Khalil, Dania; et al.
Abstract : Background: Inherited cystic kidney disorders are a common cause of end-stage renal disease. Over 50 ciliopathy genes, which encode proteins that influence the structure and function of the primary cilia, are implicated in cystic kidney disease. Methods: To define the phenotype and genotype of cystic kidney disease in fetuses and neonates, we correlated antenatal ultrasound examination and postnatal renal ultrasound examination with targeted exon sequencing, using a renal gene panel. A cohort of 44 families in whom antenatal renal ultrasound scanning findings in affected cases included bilateral cystic kidney disease, echogenic kidneys or enlarged kidneys was investigated. Results: In this cohort, disease phenotypes were severe with 36 cases of stillbirth or perinatal death. Extra renal malformations, including encephalocele, polydactyly and heart malformations, consistent with ciliopathy phenotypes, were frequently detected. Renal gene panel testing identified causative mutations in 21 out of 34 families (62%), where patient and parental DNA was available. In the remaining 10 families, where only parental DNA was available, 7 inferred causative mutations were found. Together, mutations were found in 12 different genes with a total of 13 novel pathogenic variants, including an inferred novel variant in NEK8 . Mutations in CC2D2A were the most common cause of an antenatal cystic kidney disease and a suspected ciliopathy in our cohort. Conclusions: In families with ciliopathy phenotypes, mutational analysis using a targeted renal gene panel allows a rapid molecular diagnosis and provides important information for patients, parents and their physicians.